Patrick - Rennie, Gillian (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
Patrick had to go. I decreed it. I had allowed him to move into my garage one winter but then I evicted him. Not immediately, but after his tobacco and other noxious habits had begun to unsettle my equilibrium. Also, it was becoming unsanitary for reasons I’m sure I need not explain. I granted him refuge and then I ejected him. I sent him back to the streets, towards a world of bandits with no suburban carport for safe harbour. However, when I stood outside my house, arms akimbo for courage, I said nothing of my personal discomfort. In truth I said that I was worried about the way he struck matches and smoked while lying beneath my car. I recall no resistance, only mute acceptance. He left a bag of things – aging plastic packets, a woman’s wide-brimmed straw hat now lopsided and limp, food I’d given him days before. He’d return periodically to tell me he would be back the next day to remove it. Every ‘next day’ I circled his midden, noting how its contents had expanded: a shoe, a few more plastic bundles, food I’d given him the day before, an empty matchbox. Then quickly I walked away from its smell of Patrick. I was walking away from my own shame but, being the one more mute, knew not how to say it.